Carrier Transport and Recombination in Efficient "All‐Small‐Molecule" Solar Cells with the Nonfullerene Acceptor IDTBR. Issue 19 (3rd April 2018) - Liang, Ru‐Ze; Babics, Maxime; Savikhin, Victoria; Zhang, Weimin; Le Corre, Vincent M.; Lopatin, Sergei; Kan, Zhipeng; Firdaus, Yuliar; Liu, Shengjian; McCulloch, Iain; Toney, Michael F.; Beaujuge, Pierre M.
Abstract: Reaching device efficiencies that can rival those of polymer‐fullerene Bulk Heterojunction (BHJ) solar cells (>10%) remains challenging with the "All‐Small‐Molecule" (All‐SM) approach, in part because of (i) the morphological limitations that prevail in the absence of polymer and (ii) the difficulty to raise and balance out carrier mobilities across the active layer. In this report, the authors show that blends of the SM donor DR3TBDTT (DR3) and the nonfullerene SM acceptor O‐IDTBR are conducive to "All‐SM" BHJ solar cells with high open‐circuit voltages ( V OC ) >1.1 V and PCEs as high as 6.4% (avg. 6.1%) when the active layers are subjected to a post‐processing solvent vapor‐annealing (SVA) step with dimethyl disulfide (DMDS). Combining electron energy loss spectroscopy (EELS) analyses and systematic carrier recombination examinations, the authors show that SVA treatments with DMDS play a determining role in improving charge transport and reducing non‐geminate recombination for the DR3:O‐IDTBR system. Correlating the experimental results and device simulations, it is found that substantially higher BHJ solar cell efficiencies of >12% can be achieved if the IQE and carrier mobilities of the active layer are increased to >85% and >10 −4 cm 2 V −1 s −1, respectively, while suppressing the recombination rate constant k to <10 −12 cm 3 s −1 . Abstract : Nonfullerene "All‐Small‐Molecule" Bulk Heterojunction (BHJ) solar cells with the donor DR3TBDTT and the nonfullerene acceptor O‐IDTBR yield high open‐circuit voltages >1.1V and power conversion efficiencies >6% when the active layers are subjected to solvent vapor‐annealing protocols. Experimental results correlated with device simulations show substantially higher BHJ photovoltaics efficiencies of >12% may be achievable with the DR3TBDTT:O‐IDTBR system.